Green and eco-friendly mica/Fe3O4 as an efficient nanocatalyst for the multicomponent synthesis of 2-amino-4H-chromene derivatives. Issue 1 (2nd January 2021) - Maleki, Ali; Hajizadeh, Zoleikha; Valadi, Kobra
ABSTRACT: Mica/Fe3 O4 nanocomposite was easily synthesized under the mild conditions and completely identified by Fourier transform infrared (FT-IR) spectra, field-emission scanning electron microscopy (FE-SEM) images, X-ray diffraction (XRD) pattern, energy-dispersive X-ray (EDX) analysis, thermogravimetric analysis (TGA) curve and vibrating sample magnetometer (VSM) curve analyses. Also, to environment-friendly, low cost and non-toxic features, this nanocomposite has unique physical and chemical properties such as magnetic separation, thermal stability and uniform size distribution. Then, the activity of mica/Fe3 O4 magnetic nanocomposites as an efficient heterogeneous nanocatalyst was investigated in the synthesis of 2-amino-4 H -chromene derivatives as an important group of organic pharmaceutical compounds. The catalyst can be separated by an external magnet and reused in numerous cycles without loss of its catalytic activity as well as maintenance of its stability. Green and highly efficient catalyst based on mica and mild reaction conditions is further advantages of the present work. GRAPHICAL ABSTRACT: UF0001